Linguistic and Stylistic Characteristics of the Inaugural Address (Illustrated with an Example of President Petro Poroshenko’s Inaugural Speech) (Linguostylistic Studies, 2015)
The paper analyzes the inaugural address as a separate genre at the border of two styles – official documents style and publicistic style. The author also refers to structural elements of the inaugural address and shows the issues to be carefully and precisely analyzed.  Moreover, it describes the characteristic elements distinguishing President Petro Poroshenko’s address given at the Verkhovna Rada of Ukraine on June 7, 2014, that is: occurrence of key words different from the examples used in his previous speeches, repetition, different types of expressions (from very polite to very emotive ones), a number of simple clauses, as well as non-typical endings (Peace be with us! May God bless us! Glory to Ukraine!). Apart from that, there are metaphors and quotations which have become characteristic for this very first President Poroshenko’ speech after his election. Key words: style, official documents style, inaugural speech, key words. References